Species abundance and the distribution of specialization in host-parasite interaction networks - Vazquez, Diego P. (2005)
1.Recent studies have evaluated the distribution of specialization in species interactionnetworks. Species abundance patterns have been hypothesized to determine observedtopological patterns. We evaluate this hypothesis in the context of host–parasiteinteraction networks.2.We used two independent series of data sets, one consisting of data for seven sitesdescribing interactions between freshwater fish and their metazoan parasites andanother consisting of data for 25 localities describing interactions between fleas andtheir mammalian hosts. We evaluated the influence of species abundance patterns on thedistribution of specialization in these host–parasite interaction networks with the aidof null models.3.In parallel with recent studies of plant–animal mutualistic networks, our analysessuggest that host–parasite interactions in these systems are highly asymmetric: specialistparasites tend to interact with hosts with high parasite richness, whereas hosts with lowparasite richness tend to interact mainly with generalist parasites.4.The observed distribution of specialization was predicted by a null model that assumedthat species-specific probabilities of being assigned a link during the randomizationprocess were roughly proportional to their relative abundance. Thus, abundant hoststend to harbour richer parasite faunas, with a high proportion of rare specialists.